Atticus’ Amaltheum: Attempt of Reconstruction - Bugaeva, Natalia V. (Actual Problems of Theory and History of Art, 2019)
The article is devoted to the problem of Amaltheum, known by Cicero’s mention at thecorrespondence and De legibus. N. V. Bugaeva doesn’t deny existence of such a component of Arpinum, but deals only with Atticus’ Amaltheum. There is a wide-spread opinion that Cicero’s friend created the memorial complex in Buthrotum, embodying the “ideal Rome”. Its characteristic feature was the chain of great Romans busts accompanied by short poetic inscriptions. But the evidence of Cornelius Nepos is not complete and concerns the later period of Atticus’s life; it is connected with Amaltheum very indirectly and the hypothesis of prominent compatriots lineal selection is under discussion. The most fruitful part of G. Sauron’s conceptionis the idea of safe refuge. Though the image of Zeus’ nurse or her attribute (grotto?) was the characteristic feature of Amaltheum, there is no evidence of the path fringed with great men sculptures or busts. According to N. V. Bugaeva, Amaltheum was the platane trees grove close to river without any structures (like pavilions).